1984
DOI: 10.1159/000176796
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Intake, Sunlight Exposure and 25-Hydroxyvitamin D Levels in the Elderly during One Year

Abstract: 3 groups of elderly people (65–80 years) were studied as regards their serum 25-hydroxyvitamin D (25-OH-D) concentrations, their dietary vitamin D intake and sunlight exposure during 1 year: group 1 (long-stay geriatric patients); group 2 (residents at an old people’s home), and group 3 (elderly people living in their own homes). Young adults (30–50 years) served as controls. The 25-OH-D concentration in group 1 was significantly lower during the whole year than in any other group and the concentration in grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 11 publications
4
40
1
Order By: Relevance
“…The average dietary vitamin D intake of girls aged 12 or 15 y in Finland has previously been reported to be 2.1 to 3.0 mgad; the total intake of girls of this age including supplements ranged from 2.5 to 3.4 mgad (Lamberg-Allardt, 1984). These ®gures agree with the present study ( Figure 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The average dietary vitamin D intake of girls aged 12 or 15 y in Finland has previously been reported to be 2.1 to 3.0 mgad; the total intake of girls of this age including supplements ranged from 2.5 to 3.4 mgad (Lamberg-Allardt, 1984). These ®gures agree with the present study ( Figure 1).…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have shown a signi®cant correlation between the dietary vitamin D intake and the serum 25-hydroxyvitamin D [S-25(OH)D] concentration in the elderly (Lips et al, 1987;Krall et al, 1989;Salamone et al, 1993;Thomas et al, 1998). Vitamin D from the diet is clearly important in the northern countries like Finland (Lamberg-Allardt, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown a significant correlation between the dietary vitamin D intake and the 25-hydroxy-vitamin D concentration in serum, indicating that dietary vitamin D is of importance at least in the Scandinavian countries with a low UV-light during the winter season (Haddad & Hahn, 1973;Lamberg-Allardt, 1984;Lehtonen-Veromaa et al, 1999). Circulating vitamin D concentrations reach their nadir in the winter months, and at that time the dietary intake of vitamin D has a greater impact on vitamin D status (Davies et al, 1999;Lehtonen-Veromaa et al, 1999, 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted during February to March and April to May in 1995 for low-income and high-income women, respectively. There is no difference in sunshine during this period that could substantially affect vitamin D status (Lamberg-Allardt, 1984).…”
Section: Subjectsmentioning
confidence: 90%